KAJIAN ANALISIS PESAN MORAL TENTANG KEBERANIAN PEREMPUAN DALAM FILM TABAYYUN KARYA ILYAS BACHTIAR - Artika, Yovi; Malik, Abdul; Suhardi; Irawan, Dody; Leo Shanty, Isnaini; Zaitun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of the Indonesian film industry has positioned film not onlyas a medium of entertainment but also as a form of mass communication capableof conveying social and moral values. One of the films that presents these values isTabayyun directed by Ilyas Bachtiar, which portrays women's courage in confrontingsocial pressure, defending truth, and maintaining personal integrity. This study aimsto analyze the moral messages regarding women's courage represented in the filmTabayyun. A qualitative descriptive approach employing content analysis wasapplied. The data source consisted of scenes, dialogues, character actions, andvisual elements contained in the film. Data were collected through observation anddocumentation, then analyzed by identifying, classifying, interpreting, anddescribing moral messages based on three dimensions: the relationship betweenhumans and God, the relationship with oneself, and the relationship with others. Thefindings reveal 47 moral message data, with the most dominant category being therelationship between humans and others, followed by the relationship with oneselfand the relationship with God. Women's courage is represented through moralfirmness, honesty, responsibility, resilience in facing social pressure, andcommitment to truth. These findings indicate that Tabayyun constructs women'scourage not merely as physical bravery but as moral and psychological strength thatreflects universal values relevant to contemporary society. The study contributes tocommunication studies by enriching discussions on moral messages and therepresentation of women in Indonesian films.